1982
DOI: 10.1289/ehp.824341
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of immunotoxicity

Abstract: The organs, tissues, and cells of the lymphoreticular system have received considerable attention as targets for chemicals causing adverse effects. A basic toxicological approach is described for assessing the risk of a chemical perturbing the immune system. CD-1 mice were exposed for 14 or 90 days to one of several chlorinated hydrocarbons: 1,2-dichloroethane, 1,2-dichloroethylene or 1,1,2-trichloroethylene. Other mice were exposed to dexamethasone, a known immunosuppressive agent. The immune system is evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…DEX treatment resulted in a slightly reduced body weight gain in minipigs. Similar results have been found in rodent studies [36,42]. DEX did not bring about an effect on spleen weights in the minipig.…”
Section: Effects On Growth Organ Weights and Histopathologysupporting
confidence: 90%
See 4 more Smart Citations
“…DEX treatment resulted in a slightly reduced body weight gain in minipigs. Similar results have been found in rodent studies [36,42]. DEX did not bring about an effect on spleen weights in the minipig.…”
Section: Effects On Growth Organ Weights and Histopathologysupporting
confidence: 90%
“…In contrary, Exon et al [42,43] using different DEX treatment schedules in male Sprague Dawley rats, observed a decreased DTH response to BSA. Also in a mice study of Munson et al [36] the DTH response to SRBC was found to be reduced upon DEX exposure levels up to 0.49 mg/kg in the drinking water for 90 days.…”
Section: Dth Responsesmentioning
confidence: 89%
See 3 more Smart Citations